The Influence of Professional Development on Professional Learning Community in Schools - Yasim, Jeffri Mat; Hamid, Aida Hanim A.; Mansor, Azlin Norhaini (International Journal of Psychosocial Rehabilitation, 2020)
The development of professionalism is crucial in enhancing the competency of an individual in order to strengthen educational organization. Professional learning communities (PLCs) can be considered as one of the activity under professional development that helps to improve the quality of leadership, teachers teaching and students learning. The ability to develop professionalism in implementing PLC practices among school leaders and teachers can help to improve students’ academic performance and the quality of national education. Previous studies have shown that the development of professionalism is crucial in enhancing teachers’ skills and expertise. Even the development of professionalism is also able to inculcate better understand in the professional development among PLC leaders and teachers. Therefore, a study on the role of professionalism in PLC implementation in schools should be undertaken. Hence, this study aims to identify the level of professional development and PLC practices in selected Malaysian schools. It also attempts to seek the relationship between the professional development and PLCs. The findings show that the level of professional development is high among head teachers as well as the PLCs practices. It is also found there is a positive correlation between professional development and PLCs in schools. This study is useful for head teachers and policymakers to plan for engaging PLCs for all teachers.